Monster math picnic - Maccarone, Grace; Burns, Marilyn, 1941-; Hartelius, Margaret A. (New York : Scholastic, 1998)
The number of monsters engaged in various activities at a picnic always adds up to ten. Includes related activities.
"A math reader!"--Cover.
"Cartwheel books."
Booklist.
School Library Journal.
1.0
K-3
Keywords: Counting; Monsters -- Fiction; Stories in rhyme; Board books for children, English; Counting; Monsters -- Fiction; Stories in rhyme; Reading training, English (Elementary).